Analytical Thinking Skill and Problem Solving Skills Instruments in Biology Learning Using Rasch Model - Ardianti, Riska; Razak, Abdul; Alberida, Heffi; Fadilah, Muhyiatul; Sari, Mutia (LPPM Undiksha, 2024)
The low level of analytical thinking and problem-solving skills of students is often caused by the lack of teacher evaluation of these skill levels and the inadequate use of assessment instruments. To overcome this problem, it is necessary to prepare and analyze quality instruments in order to accurately describe students' abilities. This study aims to analyze students' analytical thinking skills and problem-solving skills using Rasch modeling. This study is a quantitative descriptive research with a sample of 30 grade XI students of SMA who were selected using random sampling techniques. The research instrument consisted of eight essay questions, namely four questions to measure analytical thinking skills and four questions for problem-solving skills. Data analysis was carried out using Rasch modeling to evaluate the validity, reliability, level of difficulty, and differentiation of the questions. The results of the study show that the instrument has good to excellent validity. All items meet the fit criteria, with item reliability in the good to special category, although the reliability of the person is classified as low to sufficient. The difficulty level of the questions is ideally distributed, reflecting the balance between easy and difficult questions, as well as the excellent differentiation of items. This instrument is feasible to use, but it is recommended to increase the number of question items in order to increase the reliability of the person in the separate measurement. The implication of this study is the importance of developing valid and reliable assessment instruments to support the skill-based learning and evaluation process.